Review article. (17th December 2018) - Laing, Dave
Abstract : This review article discusses several books dealing with aspects of live music, notably festivals and arena concerts. It points out that, for the most part, two edited collections on festivals are purely celebratory and focus on audience experience rather than the character of performances. In contrast, two book-length studies of individual folk and rock festivals provide a more comprehensive account, including the extent of local opposition to the staging of the 1970 Isle of Wight Festival. Finally, the article finds much to commend in an edited volume on the arena concert. George MacKay, ed. The Pop Festival: History, Music, Media, Culture. London: Bloomsbury, 2015. xx + 234 pp. ISBN 978-1-62356-959-4 (pbk). Andy Bennett, Jodie Taylor and Ian Woodward (eds). The Festivalisation of Culture. Farnham, Surrey: Ashgate, 2014. xiii + 279 pp. ISBN 978-1-4094-3198-5 (hbk). Ray Foulk with Caroline Foulk. The Last Great Event: When the World Came to the Isle of Wight. Surbiton, Surrey: Medina Publishing, 2015. xx + 364 pp. ISBN 978-1-909339-58-3 (pbk). Derek Schofield. Towersey Festival: 50 Years in the Making. Matlock: Mrs Casey Music, 2014. iv + 172 pp. ISBN 978-0-9547502-1-3 (pbk). Robert Edgar, Kirsty Fairclough-Isaacs, Benjamin Halligan and Nicola Spelman (eds). The Arena Concert: Music, Media and Mass Entertainment. London: Bloomsbury, 2015. xv + 331 pp. ISBN 978-1-6289-2555-5 (pbk).